KONSELING KELOMPOK MODEL KIPAS (KONSELING INTENSIF, PROGRESIF, ADAPTIF, TERSTRUKTUR) UNTUK MENINGKATKAN MINAT BERWIRAUSAHA SISWA SMK DI MASA PANDEMI COVID-19 - Gudnanto Gudnanto; Edris Zamroni; Susilo Rahardjo (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Interest in entrepreneurship is an important thing that students must have in developing new entrepreneurs during this Pandemic. It is known that this pandemic period has had a significant impact on economic activity so that several sectors must be affected and reduce the opportunity to open job vacancies. Vocational students who usually rely on job vacancies should be encouraged to be interested in entrepreneurship. To increase interest in entrepreneurship, group counseling activities are needed that can help students identify, initiate, and be sure of the decisions that have been taken to become entrepreneurship. The KIPAS (Intensive, Progressive, Adaptive, Structured Counseling) counseling model is an alternative group counseling model that can provide discussion partners, innovations, and support for students who want to start a new business. This study aims to determine the effectiveness of the KIPAS model group counseling in increasing the interest in entrepreneurship in vocational students. The study was designed with a single subject design involving ten students as group members. The instrument used is a student's entrepreneurship interest scale which consists of 24 items with six leading indicators that have been empirically validated. Furthermore, the study results were tested using the Wilcoxon test with the help of SPSS 22. The results of this study indicate that the KIPAS model group counseling effectively increases the entrepreneurial interest of SMK students. The problem of limiting activities experienced by the COVID-19 Pandemic can later be overcome with group counseling that is designed in a blended manner.